2011
DOI: 10.1136/thoraxjnl-2011-200332
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnoea severity and pneumonia as predictors of in-hospital mortality and early readmission in acute exacerbations of COPD

Abstract: Background Rates of mortality and readmission are high in patients hospitalised with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). In this population, the prognostic value of the Medical Research Council Dyspnoea Scale (MRCD) is uncertain, and an extended MRCD (eMRCD) scale has been proposed to improve its utility. Coexistent pneumonia is common and, although the CURB-65 prediction tool is used, its discriminatory value has not been reported. Methods Clinical and demographic data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
6
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 19 publications
5
111
6
5
Order By: Relevance
“…Among those with a prospective design, the predictors identified include: a patient's age [23], clinical characteristics such as previous admissions, FEV 1 and pCO 2 [10,24,25,26], the treatments prescribed (e.g. the long-term use of oral corticoids [23,27]) and symptoms or health-related quality of life parameters such as dyspnea, PA and general health status [12,25,27,28]. As it can be seen, our results share some of these variables but add others recorded during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Among those with a prospective design, the predictors identified include: a patient's age [23], clinical characteristics such as previous admissions, FEV 1 and pCO 2 [10,24,25,26], the treatments prescribed (e.g. the long-term use of oral corticoids [23,27]) and symptoms or health-related quality of life parameters such as dyspnea, PA and general health status [12,25,27,28]. As it can be seen, our results share some of these variables but add others recorded during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in patients hospitalized with AECOPD complicated by consolidation, the CURB-65 (Confusion, Urea, Respiratory Rate, Blood pressure, Age > 65) community acquired pneumonia prognostic score [13] is often used to risk assess and guide antibiotic therapy [14]. However, it has been recently shown that the use of CURB-65 in patients with AECOPD and consolidation is suboptimal [15]. Hence, the Dyspnea, Esinopenia, Consolidation, Acidaemia and atrial Fibrillation (DECAF) score was first introduced by Steer et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…The modified British Medical Research Council (mMRC) scale employing a self-reported questionnaire is useful for assessing dyspnea and disability, and it's reliability has been confirmed (1,5,6). However, evidence of the relationship between the findings of dyspnea and disability and the incidence of hospitalization and exacerbation is limited, although dyspnea is known to be associated with mortality in COPD patients as a whole (7)(8)(9). In the present study, we evaluated the utility of the mMRC scale for predicting mor-tality, hospitalization and exacerbation as a consequence of the level of dyspnea (mMRC scale) and airflow obstruction (spirometric GOLD classification) in Japanese patients with COPD.…”
Section: Introductionmentioning
confidence: 99%